Adaptation of breakfast serving mechanism during Covid-19, and management of food surplus in two-star hotel (Case study on Amaris Hotel, Bandung) - Gilang Pratama Saragi; Meti Ekayani; Drajat Martianto (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Covid-19 conditions force hotels to change the mechanism of breakfast serving system, which was previously done in a buffet. This is because buffet breakfast is the time for hotel guests to gather with each other, but this is not in accordance with the Covid-19 health protocol. Besides, the buffet method also caused food surplus because the hotel had to prepare more food than the number of guests. The food surplus has the potential to become food waste if not utilised. The purpose of this research was to provide an overview of the amount of food loss from the producer side, both in terms of resources and the economy from buffet breakfast activities at hotel, and provide options for breakfast serving at hotels during the Covid-19 pandemic. This research was conducted at a two-star hotel in Bandung using survey, observation, and interview methods. The results of this research indicated that the breakfast serving method during a pandemic could be done by room service mechanism. The potential for food waste from food surplus comes mostly from the main course menu, especially carbohydrate (rice) group with 48%. If food surplus is not managed, it could become a large loss potential in both resources and economic. What is significant from this research is that this research was carried out from the producer's side, by managing the food surplus from the serving container and not from the hotel guest plate. Thus, the research results can be used as a reference for environmentally friendly hotel management.